Microinjection of antisense oligonucleotides into living mouse testis enables lncRNA function study - Zhaohui Chen; Li Ling; Xiaolian Shi; Wu Li; Huicong Zhai; Zhenlong Kang; Bangjin Zheng; Jiaqi Zhu; Suni Ye; Hao Wang; Lingxiu Tong; Juan Ni; et al. (Cell & Bioscience, 2021)
Abstract Background Long non-coding RNAs (lncRNAs) have been the focus of ongoing research in a diversity of cellular processes. LncRNAs are abundant in mammalian testis, but their biological function remains poorly known. Results Here, we established an antisense oligonucleotides (ASOs)-based targeting approach that can efficiently knock down lncRNA in living mouse testis. We cloned the full-length transcript of lncRNA Tsx (testis-specific X-linked) and defined its testicular localization pattern. Microinjection of ASOs through seminiferous tubules in vivo significantly lowered the Tsx levels in both nucleus and cytoplasm. This effect lasted no less than 10 days, conducive to the generation and maintenance of phenotype. Importantly, ASOs performed better in depleting the nuclear Tsx and sustained longer effect than small interfering RNAs (siRNAs). In addition to the observation of an elevated number of apoptotic germ cells upon ASOs injection, which recapitulates the documented description of Tsx knockout, we also found a specific loss of meiotic spermatocytes despite overall no impact on meiosis and male fertility. Conclusions Our study detailed the characterization of Tsx and illustrates ASOs as an advantageous tool to functionally interrogate lncRNAs in spermatogenesis.